1995
DOI: 10.1007/bf02116523
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hantavirus antibodies in Germany as determined by a new recombinant enzyme immunoassay

Abstract: In order to elucidate the epidemiological importance of hemorrhagic fever with renal syndrome in Germany, the prevalence of antibodies against hantaviruses was determined in 13,358 sera from residents of various geographic regions, 1,284 sera from occupational risk groups and 287 sera from chronic hemodialysis patients. Serological investigations were performed using a highly specific transferable solid phase enzyme immunoassay based on the recombinant nucleocapsid proteins of a Hantaan and a Puumala serotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
12

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 35 publications
4
66
1
12
Order By: Relevance
“…The present seroprevalence of PUUV (0.4%; 95%CI 0.1–2.3%) is comparable to the seroprevalence estimated in the Dutch (1.7%; 95%CI 1.3–2.3%), Belgian (1.5%) and German (1–3%) general population [1416]. The only orthohantavirus found in our study was identified as PUUV which is believed to cause the majority of human orthohantavirus infections in the Netherlands [14], and is associated with bank voles ( Myodes glareolus ).…”
Section: Discussionsupporting
confidence: 78%
“…The present seroprevalence of PUUV (0.4%; 95%CI 0.1–2.3%) is comparable to the seroprevalence estimated in the Dutch (1.7%; 95%CI 1.3–2.3%), Belgian (1.5%) and German (1–3%) general population [1416]. The only orthohantavirus found in our study was identified as PUUV which is believed to cause the majority of human orthohantavirus infections in the Netherlands [14], and is associated with bank voles ( Myodes glareolus ).…”
Section: Discussionsupporting
confidence: 78%
“…In einer ersten großen Seroprävalenzstudie untersuchten Zöller et al [34] [10]. In Skandinavien haben epidemiologische Untersuchungen einen Anstieg der Rötelmaus-Populationsgröße in einem mehrjährigen Zyklus gezeigt, der mit der Häufigkeit von NE-Fällen korreliert [11].…”
Section: Seroprävalenzunclassified
“…Serologische Untersuchungen legten nahe, dass in Deutschland Infektionen mit PUUV-und HTNV-verwandten Hantaviren vorkommen [34]. In Übereinstim-mung damit wurde bei über 90% der an das RKI gemeldeten Hantavirusinfektionen PUUV als Erreger angegeben.…”
Section: Infektionen Mit Puumalaund Dobravavirusunclassified
See 2 more Smart Citations